If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23x + 30 = 53 Reorder the terms: 30 + 23x = 53 Solving 30 + 23x = 53 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-30' to each side of the equation. 30 + -30 + 23x = 53 + -30 Combine like terms: 30 + -30 = 0 0 + 23x = 53 + -30 23x = 53 + -30 Combine like terms: 53 + -30 = 23 23x = 23 Divide each side by '23'. x = 1 Simplifying x = 1
| 6a+4=8a-2 | | 9z=15z | | 334+x=345 | | -3p+4=4x-3(x+2) | | x^2+2x+19=0 | | 4r+2+5r-12=15 | | x^2-3x+6x-18=0 | | 4x-25=4(x+3) | | 0.2x^3+0.5x^3-0.4x^3=0 | | 25w^2+30w+9=0 | | -8y+3(y-5)=-5(y+3) | | 4(3x-5)+7=2(6x+7) | | 5y-9+y+37=6y+30-2y | | -5x^2+4+18=0 | | 12x^2+8=104 | | -5x-7=-7x+13 | | 10y-3=7 | | -8x-11x=133 | | q-5=35 | | 4+4m=-m-1 | | 12x^2=6-x | | -5.5x=110.0 | | 3=-3x | | (4x^4+2n)-(8x^4+14n)= | | -5.5=110.0 | | -(3x-2)=3x | | 5z^6-(-3z^6-3v)= | | 6x+4y+xy+24= | | (-2w^4+11v)-(-15w^4)= | | -23+x=x+15 | | 3+2(2x-3)=1 | | 8x^9-(6x^9-7)= |